Differences in evaluation methods of trunk sway using different MoCap systems - Kutilek, Patrik; Socha, Vladimir; Cakrt, Ondrej; Svoboda, Zdenek (Acta of bioengineering and biomechanics, 2014)
The position of the trunk can be negatively influenced by many diseases. Several methods can be used for identifying defects in balance and coordination as a result of pathology of the musculoskeletal or nervous system. The aim of this article is to examine the relationship between the three methods used for analysis of trunk sway and compare two fundamentally different MoCap systems. We used a camera system and a 3DOF orientation tracker placed on subject's trunk, and measured inclination (roll) and flexion (pitch) during quiet stance. Ten healthy participants in the study were measured with eyes open and closed. The pitch versus roll plots of trunk were formed, and the area of the convex hull, area of confidence ellipse and total length of the trajectory of the pitch versus roll plot were calculated. The statistical analysis was performed and strong correlation between the area of the convex hull and area of the confidence ellipse was found. Also, the results show moderate correlation between the area of the confidence ellipse and total length of the trace, and moderate correlation between the area of the convex hull and total length of the trace. In general, the different MoCap systems show different areas and lengths but lead to the same conclusions. Statistical analysis of the participants with eyes open and eye closed did not show significant difference in the areas and total lengths of the pitch versus roll plots.
Keywords: Physiology; biomechanika; Biomechanical Phenomena; postura těla; Evaluation Studies as Topic; oči; Young Adult; Posture; Humans; hodnotící studie jako téma; mladý dospělý; fyziologie; Eye; trup; Torso; lidé